Aggregate and welfare effects of redistribution of wealth under inflation and price-level targeting - Césaire A. Meh; José-Víctor Ríos-Rull; Yaz Terajima (Bank of Canada, 2008)
Since the work of Doepke and Schneider (2006a) and Meh and Terajima (2008), we know that inflation causes major redistribution of wealth between households and the government, between nationals and foreigners, and between households within the same country. Two types of monetary policy, inflation targeting (IT) and price level targeting (PT), have very different implications for the price level path subsequent to a price-level shock, and consequently, have different redistributional properties which is what we explore in this paper. For Canada, we show that the magnitude of redistributions of an unexpected 1% price-level increase under IT is about three times larger than under PT. Households' and foreigners' wealth losses from a price level increase is matched by the gains of the government. Even though this redistribution is zero-sum, we observe positive effects on GDP due to the wealth loss, the lower value of the debt and its associated fiscal adjustment, and the non-linear effects on work effort of the redistribution of wealth across households. Finally, the direction of the change in the weighted welfare of households depends on the fiscal policy.
Keywords: D31; E21; E31; E44; E52; E63; 330; Economic models; Monetary policy framework; Sectoral balance sheet; Inflation: costs and benefits; Inflation targets; Inflation and prices; Geldpolitik; Inflation Targeting; Inflationsrate; Einkommensumverteilung; Vermögensverteilung; Wohlfahrtseffekt; Kanada